IMROVING STUDENTS ABILITY IN WRITING DESCRIPTIVE TEXT USING THINK TALK WRITE METHOD - Diyana Sitepu, Eli (Faculty of Tarbiyah nad Teacher Training, 2022)
The aim of this research is to improve students' ability in writing descriptive text using think talk write method at SMPN 2 Mardingding school. This research was conducted using classroom action research, which was carried out by applying 4 stages, namely planning, action, observation, and reflection. The implementation is carried out in two cycles. Where the pre-cycle results were 31%, then applied to cycle II and obtained results of 76%. Because it was not yet significant, the researchers applied cycle II and obtained very significant results with a total score of 93%.